COMPLAINTS AND CONDEMNS ON CRIMES AGAINST PUBLIC ADMINISTRATION IN PERU AND THE PUNO ANTI-CORRUPTION SYSTEM DURING THE YEAR 2018, AND PROPOSALS OF THE RIGHTS TO REDUCE ITS CRIME COMMISSION - Johnn Adrian Casazola León (2019)
The objective of the study was to evaluate, crimes against public administration, is part of the tradition of political, social and cultural thinking in our reality, which appears under the concept of corruption, doubting the capacity and stability of the judicial system in He makes legitimate and effective decisions. The studies of the processes, results, and impacts obtained in complaints and administrative convictions, are scarce or little known. In that sense, the investigation is aimed at analyzing crimes against public administration in Peru and the city of Puno, during the year 2018, and proposals for rights to reduce their criminal commission. Also, the core study is non-experimental, descriptive, whose instruments are content analysis and documentary sources.